Thermal and Electrical Conductivity of 99.9% Pure Copper Processed via Selective Electron Beam Melting - Raab, Sebastian; Guschlbauer, Ralf; Lodes, Matthias; Körner, Carolin (Advanced Engineering Materials, 2016)
This paper investigates the physical properties of 99.91% pure copper produced by Additive Manufacturing via selective electron beam melting (SEBM). Eddy current measurements and laser flash analyses are used to determine the electrical and the thermal conductivity. Electrical and thermal conductivity follow the Wiedemann-Franz law. The correlation of conductivities and porosity shows that 99.95 % dense components with nearly optimal conductivities (σ = 55.82 MS m and λ = 400.1 W m K) can be fabricated with SEBM. The small deviation from the theoretical maximum of copper (59.7 MS m) can be explained by the characteristics of the raw material and chemical impurities.